THE INFLUENCE OF CORPORATE GOVERNANCE ON EXPROPRIATION - PARAHITA, FITRIANNA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The concentrated ownership structure in Indonesia led to agency conflicts between the controlling shareholder and minority shareholder which is known as agency problem type II. This problem will lead to expropriation used by the controlling shareholder to maximize their own interest against the minority shareholders. This research primarily aims to examine the effect of corporate governance on expropriation. The population research is Indonesian public companies in 2016. Samples are selected by purposive sampling method resulting 91 samples. The research results show that corporate governance recommendations, frequency of board commissioner’s meeting and frequency of audit committee’s meeting affect to the expropriation. While, number of independent board commissioner does not affect the expropriation. This study contributes to agency theory type II which discusses conflicts between controlling and minority shareholders, which can be overcome by the use of corporate governance mechanisms. Keywords: corporate governance recommendations, frequency of board commissioner’s meeting, frequency of audit committee’s meeting, expropriation, related party transaction, agency theory type II